2019
DOI: 10.1155/2019/4271783
|View full text |Cite
|
Sign up to set email alerts
|

Number of Spanning Trees in the Sequence of Some Graphs

Abstract: In mathematics, one always tries to get new structures from given ones. This also applies to the realm of graphs, where one can generate many new graphs from a given set of graphs. In this work, using knowledge of difference equations, we drive the explicit formulas for the number of spanning trees in the sequence of some graphs generated by a triangle by electrically equivalent transformations and rules of weighted generating function. Finally, we compare the entropy of our graphs with other studied graphs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…e MSV model has been proved efficient and accurate in many situations [23]. e NP problem of multivariate stochastic volatility model can be solved by the Markov Monte Carlo method [24,25]. Many SV models have been established to solve different problems, such as nonlinear [26], mean [27], leverage [28], T-distribution [29], and two-factor [30].…”
Section: Introductionmentioning
confidence: 99%
“…e MSV model has been proved efficient and accurate in many situations [23]. e NP problem of multivariate stochastic volatility model can be solved by the Markov Monte Carlo method [24,25]. Many SV models have been established to solve different problems, such as nonlinear [26], mean [27], leverage [28], T-distribution [29], and two-factor [30].…”
Section: Introductionmentioning
confidence: 99%
“…e measurement methods of international organizations are very standard. e content of the study is nothing more than the basis, application, and influence of digital economy [19,20]. China's index has its own characteristics, reflecting the differences of concerns and ideas of different institutions and roles on digital economy.…”
Section: Related Workmentioning
confidence: 99%
“…In [12], the authors have shown that the generalized Peterson network P(n, 3) has a bounded metric dimension. Liu et al discussed many aspects of graph theory such as indices, metric dimension domination number, and so on in [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%